COMBINED MODALITY TREATMENT INCLUDING METHOTREXATE-BASED CHEMOTHERAPY FOR PRIMARY CEREBRAL NERVOUS SYSTEM LYMPHOMA: A SINGLE INSTITUTION EXPERIENCE - Giuseppina Massini; Francesco D'Alo'; Angelo Pompucci; Stefania Manfrida; Mario Balducci; Luciana Teofili; Stefan Hohaus; Luigi Maria Larocca; Roberto Marra; Sergio Storti (Mediterranean Journal of Hematology and Infectious Diseases)
Chemotherapy including high-dose methotrexate (HD-MTX), with or without radiotherapy, is standard treatment for primary cerebral nervous system lymphoma (PCNSL). It remains controversial whether addition of other drugs will add to therapeutic efficacy. We report here on 41 patients with PCNSL treated using a combined treatment modality, including HD-MTX (3.5 g/m2 for 2 cycles) prior to whole brain radiotherapy (WBRT). In 22 patients, the chemotherapy was intensified by adding high-dose cytosine arabinoside (HD-AraC) (2g/m2 for 4 doses for 2 cycles). Complete remission was obtained in 23 of 34 assessable patients (67%), and overall and disease-free survival rates were 24% and 46%, respectively, without differences between treatment groups. The addition of HD-AraC was complicated by severe infections in 17/22 (77%) patients, resulting in 3 toxic deaths. Our study indicates that addition of HD-AraC may not improve clinical outcome in PCNSL, while it increases toxicity. More targeted and less toxic therapies are warranted.